A Noble‐Metal‐Free CdS/Ni3S2@C Nanocomposite for Efficient Visible‐Light‐Driven Photocatalysis. Issue 12 (30th April 2018) - Cui, Yu; Pan, Yun‐Xiang; Qin, Haili; Cong, Huai‐Ping; Yu, Shu‐Hong
Abstract: Searching for highly efficient noble‐metal‐free visible‐light‐driven photocatalysts for hydrogen evolution has attracted much attention. Herein, a facile method for synthesis of a noble‐metal‐free CdS/Ni3 S2 @C nanocomposite by dispersing CdS quantum dots (≤5 nm) on urchin‐like Ni3 S2 coated by a 5‐nm‐thick carbon layer is reported. It can be used for highly efficient visible‐light‐driven photocatalytic H2 production from H2 O. The H2 production rate on CdS/Ni3 S2 @C (1164.7 µmol h −1 ) is about 3.5 times higher than that on the noble‐metal‐based CdS/Pt (325.2 µmol h −1 ). The CdS–carbon and carbon–Ni3 S2 interfaces are favorable for charge separation and the improved visible light absorbance could be the origin for the enhanced photocatalytic activity of CdS/Ni3 S2 @C. This work provides a model system for rationally designing efficient noble‐metal‐free photocatalysts for visible‐light‐driven photocatalysis. Abstract : A rationally designed route is developed for controlled synthesis of a noble‐metal‐free CdS/Ni3 S2 @C nanocomposite by dispersing CdS quantum dots (≤5 nm) on urchin‐like Ni3 S2 coated with a 5‐nm‐thick carbon layer. This results in highly efficient H2 production from visible‐light‐driven photocatalytic H2 O splitting.